Perceptions of Tadris Biology Students on the Implementation of SISTER as an LMS Choice at UIN Kiai Haji Achmad Siddiq Jember - Feby Firmilia Dewi; Indana Zulfah; Nabila Firdausi Suhandi; Putri Alifia Eksa (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
In a learning system, innovation is needed to improve the quality of the learning system. Innovation can be done by taking advantage of current technological developments such as e-learning programs. One of the e-learning programs used by students and lecturers is SISTER (Integrated Resource Information System). This SISTER will later be used as a source system that contains a portfolio of educators in Indonesia. This raises student perceptions of SISTER implementation. This research needs to be done because it aims to determine student perceptions of SISTER implementation as an LMS option at the UIN KHAS Jember. The research method used is a quantitative method with a descriptive research design. The data collection technique for this study was collected through a questionnaire via online using the Google form which was given to each student from the 2020, 2021, and 2022 batches. The results show that Tadris Biology students have a high perception of SISTER implementation as an LMS choice in terms of accessibility/convenience. in accessing SISTER as much as 53.3% of students stated that SISTER were easy to access and aspects of the benefits of SISTER were 19 the number of respondents' answers or around 63.3% chose to agree including the high category.